Gratitude and Prosocial Behavior in Happiness among Early Adulthood in Indonesian Context - Muhamad Taufik Hermansyah; Aprilia Nurcahyati; Patria Mukti (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Early adulthood is marked by various complex challenges that can influence happiness. In the Indonesian context, these include career decision-making, quarter-life crisis, and the desire to form meaningful romantic relationships. Objective: This study aims to examine the crucial roles of gratitude and prosocial behavior in predicting happiness among early adults aged 23–39. Method: A quantitative survey design was employed. Data were collected from 501 participants (n=501) using purposive sampling and analyzed through multiple regression and several additional analysis. Results: The findings indicate that both gratitude and prosocial behavior significantly contribute to happiness, with a combined effective contribution of 78.2%. Additional analysis revealed no significant gender differences in happiness. Conclusion: Gratitude and prosocial behavior jointly play a significant role in enhancing happiness during early adulthood. Suggestion: Future research should consider diverse respondent backgrounds such as socioeconomic status, age, and other contextual factors to further elucidate the determinants of happiness. Abstrak Latar Belakang: Fase dewasa awal memiliki beragam tantangan yang dapat mempengaruhi kebahagiaan. Jika melihat konteks di Indonesia, terdapat beberapa tantangan seperti penentuan karir, quarter life crisis dan keinginan menjalani hubungan romantis. Tujuan: Tujuan penelitian ini adalah untuk mengetahui peran syukur dan prososial terhadap kebahagiaan pada dewasa awal dengan rentang usia tertentu (23-39). Metode: Penelitian ini menggunakan metode kuantitatif survey. Analisis data penelitian menggunakan regresi berganda, dengan jumlah responden berjumlah 501 (n=501) dan beberapa analisis tambahan. Pengambilan data dilakukan dengan teknik purposive sampling. Hasil: Hasil penelitian menunjukkan terdapat peran antara syukur dan prososial dan syukur terhadap kebahagiaan. Sumbangan efektif yang diberikan kedua variabel bebas sebesar 78,2%. Analisis tambahan menunjukkan tidak adanya perbedaan kebahagiaan antara laki-laki dan perempuan. Simpulan: Syukur dan prososial sama-sama memberikan peran terhadap kebahagiaan. Saran: Penelitian selanjutnya disarankan mempertimbangkan variasi latar belakang responden seperti ekonomi dan usia serta faktor-faktor variabel lain yang mempengaruhi kebahagiaan.